Hole making process of carbon fiber reinforced polymer (CFRP) using end mill cutting tool - Rahim, E. A.; Mohid, Z.; Mat, K. C.; Jamil, M. F. M.; Koyasu, R.; Sasahara, H. (Trans Tech Publications, 2012)
This paper presents an alternative way of producing a hole by using a helical milling concept on a carbon fiber reinforced polymer (CFRP). Delamination is a major problem associated with making a hole by drilling on the CFRP. This study focused on helical milling technique using a vertical machining center in order to produce a hole. Various levels of cutting parameter such as cutting speed, feed rate and depth of cut have been chosen to observe the effect of trust force, delamination and surface roughness. The result will be used to determine on which cutting parameters give the best hole quality that will achieved by this new approached.